Peg-IFNα/ribavirin/protease inhibitor combination in hepatitis C virus associated mixed cryoglobulinemia vasculitis: results at week 24. Issue 5 (20th April 2013) - Saadoun, David; Resche Rigon, M; Thibault, V; Longuet, M; Pol, S; Blanc, F; Pialoux, G; Karras, A; Bazin-Karra, D; Cazorla, C; Vittecoq, D; Musset, L; et al.
Abstract : Background: The standard-of-care treatment of patients with hepatitis C virus (HCV)-mixed cryoglobulinemia (MC) vasculitis includes pegylated interferon α (PegIFN)-α plus ribavirin and/or rituximab. About 30–40% of patients are non-responders or relapsers to such combination. Objective: To analyse the safety and efficacy of Peg-IFNα/ribavirin/protease inhibitor combination in HCV-MC vasculitis. Patients and methods: Open-label, prospective, cohort study including 23 patients with HCV-MC vasculitis. Peg-IFNα/ribavirin was associated to telaprevir (375 mg three times daily, for 12 weeks, (n=15)) or boceprevir (800 mg three times daily, for 44 weeks, (n=8)) for 48 weeks. Results: The median age was 59 (52.5–66) years, with 48.8% women. Thirteen patients (56.5%) were complete clinical responders, and 10 (43.5%) were partial responders at week 24. The virological response (ie, HCV RNA negativation) was of 69.6% at week 24 (p=0.005). The cryoglobulin level decreased from 0.44 to 0.06 g/l (p=0.0006) and the C4 level increased from 0.09 to 0.15 g/l (p=0.045). Grades 3 and 4 adverse events (mainly anaemia, neutropenia and thrombocytopenia) were observed in 10 cases (43.5%). Twenty patients (87%) received erythropoietin, 9 (39.1%) had red cell transfusion, and 2 (8.7%) had granulocyte stimulating agents. Antiviral therapy discontinuation was required in 8 (34.7%) patients for virological non-response (n=5), virological relapse (n=2) and depression (n=1). Conclusions: Peg-IFNα/ribavirin/protease inhibitor combination seems highly effective in HCV-MC. Such therapeutic regimen should be administered cautiously considering the high rate of side effects.